Lumbar and sacral dermal sinus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
When in the lumbar and sacral region there are skin signs such as pits, scars, hamartomas and nevi of various type -angioma, lipoma, hypertrichosis, etc.- a dermal sinus should be suspected. The latter belongs to the late defects of the neural tube, due to an altered fusion of the encephalic and medullar structures and/or of the relevant covering structures -bone, meninges, muscle and aponeurosis layers and skin-.